The use of Problem Based Learning in Improving Students’ Learning Achievement - Etty Agustiningrum (Tanjungpura University, 2019)
This research was aimed at improving student learning outcomes in IPS subject on 7th grade SMP N 4 Pontianak. The research was using Problem Based Learning method. It used descriptive method with qualitative design. It was implemented through 2 cycles, in which each cycle consisted of four steps such as planning, acting, observing, and reflecting. The data collecting techniques used in this research were direct observation and students’ learning outcomes. Based on the result of analysis showed that there was an improvement in learning activity in the first cycle as 60% meanwhile the second cycle showed 71%. The student outcomes at the first cycle showed 56% and the second cycle improved to be 76,5%.